Recent Advances of Biomedical Materials for Prevention of Post-ESD Esophageal Stricture - Bao, Yuchen; Li, Zhenguang; Li, Yingze; Chen, Tao; Cheng, Yu; Xu, Meidong (Frontiers in Bioengineering and Biotechnology, 2021)
Esophageal stricture commonly occurs in patients that have suffered from endoscopic submucosal dissection (ESD), and it makes patients difficult to swallow, significantly reducing their life qualities. So far, the prevention strategies applied in clinical practice for post-ESD esophageal stricture usually bring variously inevitable complications, which drastically counteract their effectiveness. Nowadays, with the widespread investigation and application of biomedical materials, lots of novel approaches have been devised in terms of the prevention of esophageal stricture. Biomedical polymers and biomedical derived materials are the most used biomedical materials to prevent esophageal stricture after ESD. Both of biomedical polymers and biomedical derived materials possess great physicochemical properties such as biocompatibility and biodegradability. Moreover, some biomedical polymers can be used as scaffolds to promote cell growth, and biomedical derived materials have biological functions similar to natural organisms so they are important in tissue engineering. In this review, we have summarized the current approaches for preventing esophageal stricture, and put the emphasis on the discussion of the roles of biomedical polymers and biomedical derived materials acted in esophageal stricture prevention. Meanwhile, we proposed several potential methods that may be highly rational and feasible in esophageal stricture prevention based on other researches associated with biomedical materials. This review is expected to offer a significant inspiration from biomedical materials to explore more effective, safer, and more economical strategies to manage post-ESD esophageal stricture.